Mutation of recA gene of Vibrio cholerae: Towards the development of attenuated vibrio cholerae vaccine strains - Kuan, Goh Lai (2004)
Despite over hundred years of study, the intestinal pathogen Vibrio cholerae still causes epidemic outbreaks in areas of the world. The endemic areas include India, Asia, Africa, the Mediterranean, and more recently, South and Central America, Mexico and the United States (Faruque et a/, 1998). This Gram-negative bacterium cplonizes the human intestine and causes potentially fatal diarrhoeal disease- the Cholera. A number of genes associated with the virulence of Vibrios had so far been identified by researchers of cholera. These genes are gaining popularity among researchers especially in the manipulation of them towards the production of an effective cholera vaccine. In this research, however, the recA gene was the center of interest. It was reported by Ghosh et al (1985) that the Vibrio cholerae have a RecA system that is analogous to the Escherichia coli RecA system. The RecA protein is the central enzyme for homologous recombination, DNA strand exchange, and DNA repair mechanism (Kuzminov, 1999). In the development of live attenuated, oral cholera vaccine, the mutation of recA gene was strongly recommended by some researchers to render the vaccine strains recombination deficient (Goldberg and Mekalanos, 1986; Taylor et al, 1994; Kenner et al, 1995; Kaper et al, 1994; Boyd and Waldor, 1999). Hence, the general approach of study is to mutate the recA gene in existing vaccine strain (VCUSM-2) to stabilize and prevent the strain from further acquiring the undesirable gene when released to the environment. The study began with a deletional mutation in the 1.2kb Vibrio cholerae recA gene previously cloned onto the vector, pTOP02.1. The EstEll was recognized as the unique restriction enzyme site which existed twice in the middle of Vibrio cholerae recA gene at the location of 71 Obp and 782bp. Upon restriction with EstEll, a small fragment of gene with the Isize of 72bp was deleted. The sticky overhang was polished and this was followed by a selfblunt end ligation of the linearized plasmid. The deletional mutation of recA gene produced a + 1 frameshift mutation starting from the ligation junction to the down stream of recA gene. As a result a stop codon was introduced at 748bp of the gene, and hence results in a truncated recA gene product. The successfully mutated Vibrio cholerae recA gene was then subcloned onto the pBluescriptiiSK before it was transferred onto the pCVD442, a conjugatable suicide plasmid for conjugation with the cholera vaccine strain, VCUSM-2.